Penentuan Kadar Flavonoid Total Ekstrak Etanol Jamur Susu Harimau (Lignosus rhinocerus) - Sari, Dina Yuspita; R, Widyasari; AN, Taslima (Jurnal Farmasi Udayana, 2021)
ABSTRACT Tiger milk mushroom (Lignosus rhinocerus) is a plant that has traditionally been used as a medicine in the interior of West Kalimantan, especially in Kapuas Hulu. One of the phytochemical constituents contained is flavonoids (flavones and flavanones). This study aims to determine the total flavonoid content of ethanol extract of tiger milk mushroom. The simplicia of tiger milk mushroom was macerated using 96% ethanol. Phytochemical screening for the presence of flavonoids the extract using magnesium and amyl alcohol powder. Determination of total flavonoid content in ethanol extract of tiger milk mushrooms was carried out by UV-Vis spectrophotometry using the colorimetric method (AlCl?) at ? 410 nm and expressed as total flavonoids in quercetin equivalent. The results showed that total flavonoid content of ethanol extract is 33.041 mgEQ/g extract. Ethanol extract of tiger milk mushroom which contains flavonoids is potential as a source of natural antioxidants and potential to be developed in medicinal and cosmetic products. Keywords : Colorimetry, tiger milk mushroom, total flavonoid content.